Esterification of free fatty acid in used cooking oil using sulphonated hypercrosslinked exchange resin as catalyst - Nurul Asmawati, Roslan (2017)
Esterification reaction is a pretreatment method used to reduce the free fatty acids (FFA) content in acidified oil. Normally, the presence of high FFA content contributes to saponification reaction and thus, decreases the yield of fatty acid methyl ester (FAME) produced. The usage of ion exchange resin (IER) as a catalyst has been widely used to reduce the FFA content because they can catalyse the esterification reaction under mild conditions. However, current IER are having low acidic acid sites, moderate surface area and low thermal stability. This study focuses on the esterification process of FFA in simulated used cooking oil (SUCO) using self-synthesised sulphonated hypercrosslinked exchange resin (SHER) as catalyst. This study was divided into two stages. The first stage focused on the synthesis and characterisation of SHER, prepared via non-aqueous dispersion (NAD) technique followed by sulphonation process. The effect of monomer/co-monomer concentration, crosslinker concentration, Lewis acid catalyst ratio, and sulphonation reagent on the physicochemical characterisation of the resin were investigated to produce the best catalyst beads. From this stage, the best SHER beads has successfully developed at the condition of 80% of styrene (St), 20% of vinylbenzyl chloride (VBC), 1wt% of ethylene glycol dimethacrylate (EGDMA), 1:1 of molar ratio of FeCl3: CH2Cl, and 4wt% of sulphuric acid. The newly developed SHER possesses a high surface porosity with approximately 836 m2 g-1 surface area. It has the ability to withstand high temperature up to 398°C with the acidity values at 5.1 mmol g-1. The second stage concentrated on the performance of SHER in the esterification of FFA using SUCO as a feedstock. The esterification reaction was carried out in a batch system and the effect of various parameters such as catalyst loading, temperature, and molar ratio were investigated. SHER had successfully catalysed the reaction and achieved 97% of FFA conversion at 150 rpm, 5wt% of catalyst loading, 60°C, and 12:1 of methanol (MeOH) to SUCO molar ratio. During reusability study, the catalyst activity decreased for about 40% after five cycles of reaction. The decrease in FFA conversion was due to the pore blockage during the reaction and hence, blocked the reactants from accessing the active sites. The performance of SHER was compared with selected commercial resins (i.e., Diaion RCP145H, Diaion PK228LH, and Diaion SK1BH) and the experiments were conducted at the same reaction conditions. SHER showed the highest conversion and reaction rate compared to other catalysts. The excellence performance of SHER was due to the high amount of surface area, pore volume, sulphur content, and acidity owned by the SHER.